Promising Practices in the Frontiers of Quality Outcome Measurement for Intellectual and Developmental Disability Services - Bogenschutz, Matthew; Dinora, Parthenia; Lineberry, Sarah; Prohn, Seb; Broda, Michael; West, Angela (Frontiers in Rehabilitation Sciences, 2022)
Medicaid Home and Community-Based Services (HCBS) for people with intellectual and developmental disabilities (IDD) are vital for supporting people with IDD to live well in their communities, but there are not set standards for monitoring quality outcomes related to HCBS. In this paper, we propose promising practices for improving the quality of HCBS outcome measurement, based both in the literature and our own experience conducting an extensive U.S. state-level study. Specifically, we discuss: 1) using merged administrative datasets, 2) developing high-quality psychometrics that attend to ecological issues in measurement, 3) using advanced statistical analyses, and 4) creating immersive, user-friendly translational dissemination products. We conclude by suggesting what we see as important new frontiers for researchers to consider in order to enhance the quality of HCBS outcome measurement for people with IDD in the future.